2014
DOI: 10.1002/ardp.201400215
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Anti‐Cancer Activity Evaluation of New Dimethoxylated Chalcone and Flavanone Analogs

Abstract: A novel series of chalcones and flavanones discriminated by the presence of a 3,4-dimethoxyphenyl moiety in their structures were synthesized as anti-cancer agents. The cytotoxicity evaluation of the analogs against the MCF-7, MDA-MB-231 (human breast cancer), and SK-N-MC (human neuroblastoma) cell lines demonstrated that the introduction of a halogen on the 3,4-dimethoxyphenyl part of both series and the attachment of a pyrrolidinylethoxy group on the C-7 position of the flavanone derivatives increased their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Ketabforoosh et al found that chalcones with a 3,4-dimethoxyphenyl moiety in their structure and their derivatives with an additional chloride atom or methoxy group at carbon C-5 are much more potent inhibitors of cell growth than corresponding flavanones as observed in three different cancer cell lines—neuroblastoma cell line SK-N-MC and breast cancer cell lines: MDA-MB-231 and MCF-7. 40 In contrast, the attachment of a pyrrolidinylmethoxy group at position C-7 of a flavanone structure increased the cytotoxicity of flavanones when compared to their parent chalcone.…”
Section: Discussionmentioning
confidence: 99%
“…Ketabforoosh et al found that chalcones with a 3,4-dimethoxyphenyl moiety in their structure and their derivatives with an additional chloride atom or methoxy group at carbon C-5 are much more potent inhibitors of cell growth than corresponding flavanones as observed in three different cancer cell lines—neuroblastoma cell line SK-N-MC and breast cancer cell lines: MDA-MB-231 and MCF-7. 40 In contrast, the attachment of a pyrrolidinylmethoxy group at position C-7 of a flavanone structure increased the cytotoxicity of flavanones when compared to their parent chalcone.…”
Section: Discussionmentioning
confidence: 99%
“…Flavanones, including naringenin, pinocembrin and eriodictyol, are the first flavonoid products in flavonoids biosynthetic pathway. They are generally present in citrus fruits, such as grapefruit (Peterson et al, 2006), oranges (Khan et al, 2010), and lemons (Peterson et al, 2006) and have anti-inflammatory (Bano et al, 2013), antioxidant (Miranda et al, 2000), anticancer (Ketabforoosh et al, 2014), and other important pharmacological activities. The basic skeleton of flavanones is 2-phenylchromogen, which is characterized by the saturation of the C2-C3 double bond.…”
Section: Flavanonesmentioning
confidence: 99%
“…They were synthesized as described with some modifications (Ketabforoosh et al, 2014). To a stirred solution of chalcone (1 equiv.)…”
Section: General Procedures For the Synthesis Of Flavanones 3 4 Andmentioning
confidence: 99%
“…The reaction mixtures were heated under reflux for 6 h. and then allowed cooling to room temperature. After work-up the flavanone mixtures were purified by column chromatography using hexanes-ethyl acetate mixtures of increasing polarity (Ketabforoosh et al, 2014). The OMOM groups were hydrolyzed with 1N HCl in methanol under reflux for 15 min longer hydrolysis times lowered yield.…”
Section: General Procedures For the Synthesis Of Flavanones 3 4 Andmentioning
confidence: 99%